Additive Enhanced Crystallization of Solution‐Processed Perovskite for Highly Efficient Planar‐Heterojunction Solar Cells. (14th March 2014) - Liang, Po‐Wei; Liao, Chien‐Yi; Chueh, Chu‐Chen; Zuo, Fan; Williams, Spencer T.; Xin, Xu‐Kai; Lin, Jiangjen; Jen, Alex K.‐Y.
<x xml:space="preserve">Abstract</x> An effective method to control the rate of perovskite crystallization by incorporating rationally chosen additives into the perovskite precursor solutions is demonstrated. The processing additives simultaneously facilitate nucleation and modulate the kinetics of crystal growth during crystallization, leading to much smoother perovskite morphology with improved coverage area and crystal uniformity. As a result, it enables very high PCE (∼12%) planar‐heterojunction solar cells to be fabricated through the low‐temperature solution processes (under 150 °C). This study opens up a new direction for optimizing perovskite active layer properties to expand device performance ceilings. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>